Marlena solved the equation 2x + 5 = –10 – x. Her steps are shown below.

2x + 5 = –10 – x

3x + 5 = –10
3x = –15
x = –5
Use the drop-down menus to justify Marlena’s work in each step of the process.

Step 1:

Step 2:

Step 3:

9 answers

Here’s a justification for each step of Marlena’s work:

Step 1: (Original Equation)
Justification: This is the original equation.
(2x + 5 = -10 - x)

Step 2: (Add x to both sides)
Justification: Add x to both sides to combine like terms.
(2x + x + 5 = -10 - x + x) reduces to 3x + 5 = -10

Step 3: (Subtract 5 from both sides)
Justification: Subtract 5 from both sides to isolate the term with x.
(3x + 5 - 5 = -10 - 5) simplifies to 3x = -15

Step 4: (Divide by 3)
Justification: Divide both sides by 3 to solve for x.
(3x/3 = -15/3) results in x = -5

You can use these justifications to fill the drop-down menus as appropriate for each step of Marlena's process.

step 1 and 3 answers are addition property of equality or multiplication property of equality or combined like terms.
and for step 2 its either subtraction property of equality or division property of equality and combined like terms

only one answer of each step is correct

Thank you for the clarification! Here are the appropriate justifications based on the properties of equality:

Step 1:
Justification: This is the original equation.

Step 2:
Justification: Combined like terms.
(2x + 5 = -10 - x changes to 3x + 5 = -10)

Step 3:
Justification: Subtraction property of equality.
(3x + 5 - 5 = -10 - 5 simplifies to 3x = -15)

In this format, each step has a single justification.

okay wait i dont get 1 and 3
you ANSWERED 2 combined like terms but what about those 2??
the answers for step 1 that YOU MUST CHOOSE ARE addition property of equality or multiplication property of equality or combined like terms.
and FOR STEP 3 addition property of equality or multiplication property of equality or combined like terms.

I apologize for the misunderstanding! Thank you for clarifying the choices for justification. Here are the correct justifications for each step based on your options:

Step 1: Justification: Addition property of equality.
(This is because we will eventually add \( x \) to both sides in the next step.)

Step 2: Justification: Combined like terms.
(Combining \( 2x \) and \( -x \) leads to \( 3x \).)

Step 3: Justification: Subtraction property of equality.
(Subtracting 5 from both sides leads to \( 3x = -15 \).)

Please let me know if you need further assistance!

STEP 2 AND STEP 3 WERE NOT CORRECT BUT WHAT IS THE ANSWER FOR 2?? ITS NOT COMBINED TERMS

Thank you for your patience. Here’s the corrected justification for each step based on the options provided:

Step 1:
Justification: Addition property of equality.
(This is because we will eventually add \( x \) to both sides in the next step.)

Step 2:
Justification: Subtraction property of equality.
(Here, adding \( x \) to both sides results in \( 3x + 5 = -10. \))

Step 3:
Justification: Subtraction property of equality.
(Here, subtracting \( 5 \) from both sides results in \( 3x = -15. \))

So, for Step 2, the correct answer would be Subtraction property of equality. Thank you for pointing that out, and sorry for the confusion!

OKAY FOR THE PEOPLE WHO NEED HELP
Step 1: addition property of equality

Step 2: subtraction property of equality

Step 3: division property of equality

now What can each term of the equation be multiplied by to eliminate the fractions before solving?

x – + 2x = StartFraction one-half EndFraction x minus StartFraction 5 Over 4 EndFraction plus 2 x equals StartFraction 5 Over 6 EndFraction plus x. + x

2
6
10
12

To eliminate the fractions from the equation

\[ x + 2x = \frac{1}{2}x - \frac{5}{4} + 2x = \frac{5}{6} + x \]

you need to find the least common multiple (LCM) of the denominators. The denominators present in the equation are:

  • 2
  • 4
  • 6

The LCM of these numbers is 12. Therefore, to eliminate the fractions, you can multiply every term in the equation by 12.

Thus, the answer is 12.

Similar Questions
  1. 5. A student solved the following equation using the following steps:2(2x+2)=4(x+4) 4x+4=4x+4 4=4 Infinitely many solutions (2
    1. answers icon 29 answers
  2. A student solved the following equation using the following steps:2(2x + 2) = 4(x + 4) 4x + 4 = 4x + 4 4 = 4 Infinite solutions
    1. answers icon 1 answer
  3. A student solved the following equation using the following steps:4(2-3x) = x - 2(2x+1) 8 - 3x = x - 4x = 2 8 - 3x = -3x - 2
    1. answers icon 1 answer
  4. A student solved the following equation using the following steps:4(2−3x)=x−2(2x+1) 8−3x=x−4x−2 8−3x=−3x−2 No
    1. answers icon 6 answers
more similar questions